Positioning High-Throughput CETSA in Early Drug Discovery through Screening against B-Raf and PARP1. (February 2019) - Shaw, Joseph; Dale, Ian; Hemsley, Paul; Leach, Lindsey; Dekki, Nancy; Orme, Jonathan P.; Talbot, Verity; Narvaez, Ana J.; Bista, Michal; Martinez Molina, Daniel; Dabrowski, Michael; Main, Martin J.; et al.
Methods to measure cellular target engagement are increasingly being used in early drug discovery. The Cellular Thermal Shift Assay (CETSA) is one such method. CETSA can investigate target engagement by measuring changes in protein thermal stability upon compound binding within the intracellular environment. It can be performed in high-throughput, microplate-based formats to enable broader application to early drug discovery campaigns, though high-throughput forms of CETSA have only been reported for a limited number of targets. CETSA offers the advantage of investigating the target of interest in its physiological environment and native state, but it is not clear yet how well this technology correlates to more established and conventional cellular and biochemical approaches widely used in drug discovery. We report two novel high-throughput CETSA (CETSA HT) assays for B-Raf and PARP1, demonstrating the application of this technology to additional targets. By performing comparative analyses with other assays, we show that CETSA HT correlates well with other screening technologies and can be applied throughout various stages of hit identification and lead optimization. Our results support the use of CETSA HT as a broadly applicable and valuable methodology to help drive drug discovery campaigns to molecules that engage the intended target in cells.